The film club as audiovisual literacy in school (Revista de Ensino em Artes, Moda e Design, 2026)
The article presents the results of a cartographic field study conducted by the author between 2024 and 2025, based on film clubs and the appropriation of the triangular approach, emphasizing the axes of seeing, enjoying, discussing, analyzing, and creating as a proposal for audiovisual literacy in high school. The guiding principle of the film club project was the use of a Ludovicense film curatorship, a sociocultural context in which the research is inserted as an instrument of recognition, identity, and belonging for students, with the objectivo of promoting meaningful and emancipatory learning, in line with Freirean assumptions of a problematizing education focused on the development of critical awareness of social and political reality. The empirical field of the research covered three Educa Mais Centers (CEM) in the city of São Luís do Maranhão, full-time secondary education institutions. The investigation sought to answer the following question: how can film clubs be a viable proposal for audiovisual literacy in high school? To this end, the research analyzed both the theoretical and legal references that support teaching practice in the field of audiovisual education and the empirical data produced during the implementation of the Cineclube na Escola (Film Club at School) project.
Keywords: Triangular approach; Audiovisual literacy; Film clubs; Secondary education; Critical pedagogy